2014
DOI: 10.4314/gmj.v48i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Habits among School Children in Selected Communities in the Eastern Region of Ghana

Abstract: SUMMARYBackground: Breakfast is considered the most important meal of the day, yet many people skip breakfast. Studies indicate that school age children who regularly skip breakfast are not likely to concentrate in class, thus affecting school performance. This study determined the breakfast habits and nutrient contributions of the breakfast meal to the days' nutrient intake. Design: A cross sectional study was conducted among school children (n=359) between the ages of 6-19 years in Manya Krobo in the Eastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
0
20
2
Order By: Relevance
“…Overall, overweight appears to be a more significant challenge than underweight in this study, as it was also 4 times higher, and this implies that overweight is a greater challenge and can become a national burden in this age group if the trend continues [20]. Breakfast consumption was high among this sample, with over three quarters consuming breakfast the morning of the dietary assessment, although this was lower than reported in a previous study in Ghana, where 85.5% of school children had breakfast before school [21]. Moreover, fewer children reported a difficulty in consuming breakfast before school, suggesting that breakfast skipping was less than an issue in these children.…”
Section: Discussioncontrasting
confidence: 69%
“…Overall, overweight appears to be a more significant challenge than underweight in this study, as it was also 4 times higher, and this implies that overweight is a greater challenge and can become a national burden in this age group if the trend continues [20]. Breakfast consumption was high among this sample, with over three quarters consuming breakfast the morning of the dietary assessment, although this was lower than reported in a previous study in Ghana, where 85.5% of school children had breakfast before school [21]. Moreover, fewer children reported a difficulty in consuming breakfast before school, suggesting that breakfast skipping was less than an issue in these children.…”
Section: Discussioncontrasting
confidence: 69%
“…Although eating a regular breakfast was associated with favourable values of diastolic blood pressure and total and LDL cholesterol in our study, the differences between the sexes, energy consumption and physical activity could not be explained. Other studies have indicated that people who eat breakfast infrequently tend to eat fewer calories daily. They also have a poorer overall quality diet and an irregular distribution of energy consumption throughout the day, which, in association with missing breakfast, may be responsible for changes in their clinical and biochemical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a better overall quality of nutrition, studies suggest that the usual intake of breakfast is associated with a reduced risk of excess weight and reduced body mass index (BMI) in children and adolescents . This can mainly be attributed to the fact that children and adolescents who do not eat breakfast are less likely to have lunch and, or dinner regularly, tend to make poor food choices, consume unhealthy foods between meals, buy food outside home and be less physically active .…”
Section: Introductionmentioning
confidence: 99%
“…The Ghana school feeding programme (GSFP) introduced in 2005 in some selected schools is one of such interventions to enhance nutrition and improve school attendance and education outcomes [7]. In resource limited nations, majority of school-aged children often walk long distances to school without having a morning and midday meal due to poverty [8]. The school feeding programme therefore offers these children with at least one free meal during school hours.…”
Section: Introductionmentioning
confidence: 99%